De novo transcriptome combined with spectrophotometry and gas chromatography-mass spectrometer (GC-MS) reveals differentially expressed genes during accumulation of secondary metabolites in purple-leaf tea (Camellia sinensis cv Hongyafoshou). Issue 3 (4th May 2019) - Guo, Yuqiong; Chang, Xiaojun; Zhu, Chen; Zhang, Shuting; Li, Xiaozhen; Fu, Haifeng; Chen, Changsong; Lin, Yuling; Lai, Zhongxiong
ABSTRACT: To investigate differences in secondary metabolites and their related molecular mechanisms between purple-leaf tea and green-leaf tea, the transcriptomes and the secondary product profiles of the Camellia sinensis cultivars 'Hongyafoshou' (HF) and cultivar 'Lvyafoshou' (LF) were analysed and compared using GC-MS and spectrophotometric methods. The contents of anthocyanins, carotenoids, and total catechins were higher in HF than in LF. In total, 8, 406 differentially expressed genes (DEGs) between HF and LF were identified. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses revealed that the flavonoids, carotenoids and terpenoids metabolic pathways were highly enriched with DEGs. Differences in the expression of DEGs involved in these three pathways might be responsible for the high accumulation of secondary metabolites in HF. The small miRNA miR529 plays regulatory roles in these secondary metabolic pathways. The sensory quality of purple-leaf tea is higher than that of green-leaf tea, and these results from the combination of flavonoids, carotenoids, and terpenoids biosynthesis. Our study provides further insights into the molecular mechanisms underlying differences in secondary metabolite accumulation between HF and LF.